ANALYSIS OF THEORIES JUSTIFYING THE PROTECTION OF WELL-KNOWN MARKS - Markova, Marija (Teisė, 2017)
This article analyses main theories providing the rationale for the protection of well-known marks as it is established in Article 16 (3) of the TRIPS Agreement. Article aims at answering the question if any of these theories could be considered as a doctrinal basis for the protection of well-known marks which extends beyond the principle of specialty. This analysis is also important in the light of the EU protection for trade marks with reputation which in practice is applied inconsistently and requires more detailed analysis. The separation line between the protection of well-known marks and marks with reputation in the EU is not very clear and the EU trade mark law reform has not addressed the deficiencies of the legal regulation. Once the doctrinal basis for the protection of well-known marks is established, the analysis of goals and limits of protecting reputed marks should be undertaken. Article analysis two groups of theories. The first group encompasses doctrines which mainly focus on the protection of interests of trade mark proprietors. The second group analyses the extended protection of well-known marks from the protection of the consumer’s’ interests point of view. Article covers the analysis of F. Schechter’s dilution theory and theory on the protection against unfair advantage, brand expansion theory, theory of the protection of the advertising function, search cost theory and theory on the protection of the consumers‘ „exclusivity feeling“. The conclusion is reached that all the above listed theories have disadvantages that make their practical applicability quite difficult. It is also concluded that without establishing a clear doctrinal basis for the protection of well-known marks which extends beyond the principle of specialty it becomes challenging to analyse a rationale for the protection of trade marks with reputation.